CHALLENGES OF MENTAL HEALTH ISSUES IN PREGNANT WOMEN WITH COMORBID TUBERCULOSIS: A BIBLIOMETRIC ANALYSIS: MENTAL HEALTH ISSUES IN PREGNANT WOMEN - Gerung, Jumartin; Fadmi, Fitri Rachmillah; Pati, Wisnu Catur Bayu; Noviyanti, Wa Ode Nova (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2025)
Background: Patients with tuberculosis (TB) often face stigma within their communities. Additionally, TB is frequently accompanied by comorbid conditions that contribute to psychological stress, as patients must cope with a dual burden. Pregnant women with comorbid TB are particularly vulnerable to developing mental health problems. Methods: Searching PubMed, Google Schoolar, dan Scopus from 2018 to 2023. Using Publish or Perish, a number of journals were collected and visualized using VOS viewer. Results: Various comorbid conditions have been identified in TB patients such a HIV, DM, etc. Similarly, mental health issues have been observed in pregnant women with comorbid TB. Including anxiety disorders, depression, stress, and other related mental health conditions. Conclusion: The double burden of disease on TB patients makes them feel depressed. The stigma that exists in the community makes patients isolated. Community support is needed in the midst of patients who experience a lot of psychological pressure. Therefore, efforts to prevent and treat mental health disorders in comorbid TB patients require cooperation between health workers, families and people closest to the patient.